All-Cause and Infection-Related Mortality in Staphylococcus aureus Bacteremia, a Multicenter Prospective Cohort Study. (30th November 2022) - van der Vaart, Thomas W; Prins, Jan M; Soetekouw, Robin; van Twillert, Gitte; Veenstra, Jan; Herpers, Bjorn L; Rozemeijer, Wouter; Jansen, Rogier R; Bonten, Marc J M; van der Meer, Jan T M
Abstract: Background: Staphylococcus aureus bacteremia (SAB) is a heterogeneous disease with changing epidemiology due to changing demographics and evolving clinical management. SAB is associated with high mortality, but the current fraction of infection-related mortality is less well quantified. Methods: In a multicenter prospective cohort study of consecutive patients with SAB, we determined clinical features of SAB and determined 90-day mortality and risk factors of all-cause and infection-related mortality. Infection-related mortality was based on an adjudication committee evaluation. Results: Four hundred ninety patients with SAB were included, with community-acquired (n = 166), health care–associated (n = 163), and hospital-acquired SAB (n = 161). Endocarditis (n = 90, 18.3%), peripheral intravenous catheter infection (n = 80, 16.3%), and septic arthritis (n = 58, 11.8%) were the most frequent diagnoses, but proportions differed for community, health care, and hospital acquisition. One hundred ninety-two patients (39%) had permanent implanted prosthetic material (eg, prosthetic joint, heart valve, pacemaker). Day 90 all-cause mortality was 33% (n = 161), with 60% adjudicated as infection-related, and 90% of infection-related deaths occurring in the first 30 days post-SAB. Infection-related deaths after 30 days were rare and mainly related to endocarditis. Determinants associated with day 90 infection-related mortality were age (odds ratio [OR], 1.09; 95% CI, 1.06–1.11), Charlson comorbidity index (OR, 1.13; 95% CI, 1.01–1.26), septic shock (OR, 9.78; 95% CI, 4.56–20.95), endocarditis (OR, 3.4; 95% CI, 1.75–6.61), and persistent SAB at 48 hours (OR, 2.36; 95% CI, 1.27–4.37). Conclusions: Mortality due to S. aureus infection remains high and mainly occurs in the first 30 days, which could guide end points in future studies.